Leveraging Blockchain Governance and Smart Contracts for Entrepreneurs in Social Media - Kanon Mommsen Wongkar; Triananda Fajar Satriawan; Nuke Puji Lestari Santoso; Noah Rangi (Blockchain Frontier Technology, 2026)
Social media entrepreneurship is shaped by centralized platforms controlling algorithms, monetization, and data, often limiting autonomy and bargaining power. Blockchain governance and smart contracts offer alternative arrangements to enhance transparency, trust, and value distribution. This study aims to examine the role of blockchain governance and smart contracts as alternative institutional mechanisms for entrepreneurs in social media ecosystems, with a focus on implementation conditions, strategic opportunities, and associated limitations. This research adopts a qualitative conceptual approach based on a systematic review of indexed academic literature published between 2022 and 2025, complemented by an analysis of documentation from blockchain based social media platforms, white papers, and relevant industry reports. The analysis maps key challenges faced by social media entrepreneurs onto blockchain governance mechanisms and smart contract functionalities. The findings indicate that blockchain governance and smart contracts can enhance entrepreneurial participation, improve transparency in revenue distribution, and strengthen the protection of digital assets. However, these benefits are context dependent and con- strained by several factors, including technical complexity, unequal token distribution, and regulatory uncertainty. Therefore, blockchain governance and smart contracts should not be viewed as universal solutions, but as strategic instruments whose effectiveness depends on inclusive governance design, sufficient technical readiness, and adaptive policy frameworks to support sustainable social media entrepreneurship. This article contributes by proposing an evaluative framework to assess the implementation of blockchain governance and smart contracts in social media entrepreneurship, emphasizing alignment be- tween technological design, governance inclusivity, and ecosystem readiness.